Turismo comunitario y la convivencia intercultural en la Comunidad Hacienda La Chorrera del cantón Babahoyo - Franco Sellan, Andres Eloy (2019)
The community tourism and the coexistence intercultural is the perfect combination to improve the relationships among tourist-residents, meetings should always be so that a good tourism is given in any place where it implements it to him. The community tourism contributes with the natural resources that possess the area and the coexistence intercultural with the beliefs, customs, traditions and ancestral knowledge of the community. The combination of these variables takes to the development of tourist activities that you/they will be good for the enjoyment of the tourists, satisfying its necessities, making him live an unforgettable experience. Presently case study will be about the importance of the community tourism and the coexistence intercultural in the Community Treasury The Spout, located in the Parish Pimocha of the Canton Babahoyo. To justify this topic he/she will be defined the Community Tourism conceptually. Then in the theoretical sustenance he/she will be carried out an analysis of the independent variables and clerk that reinforce the reason of this case study; subsequently the tourist activities are analyzed so much from a territorial perspective as from the traditional bid and ask analysis, and lastly, it will be exposed the obtained results of the first study of case of community tourism and coexistence intercultural that he/she has started in this area.